Probiotic potential and safety assessment of autochthonous Lentilactobacillus farraginis BDN12 from fermented okara for feed applications - NGUYEN PHUONG THUY; NGUYEN MINH THU; TRUONG THI CAM TIEN; LE NGUYEN BAO CHAU; NGO GIA HUY; LE NGOC LINH DAN; BUI NGOC THAO MY; NHAN VINH NHAT LAM; NGUYEN NHAT MINH; NGUYEN DANG KHOA; HA THI MAI HUONG; LE THAO VY; NGUYEN THUY LINH; PHAM HONG DIEP (Society for Indonesian Biodiversity, 2026)
Abstract. Thuy NP, Linh NT, Vy LT, Huong HTM, Khoa ND, Minh NN, Lam NVN, My BNT, Dan LNL, Huy NG, Chau LNB, Tien TTC, Thu NM, Diep PH. 2026. Probiotic potential and safety assessment of autochthonous Lentilactobacillus farraginis BDN12 from fermented okara for feed applications. Biodiversitas 27 (5): d270514. https://doi.org/10.13057/biodiv/d270514. The escalating risk of antimicrobial resistance has intensified the search for autochthonous probiotics as sustainable alternatives to antibiotic growth promoters in livestock. This study aimed to isolate and characterize high-performance Lactic Acid Bacteria (LAB) from fermented okara, a traditional Vietnamese soybean byproduct, for specific application in poultry feed. A hierarchical five-stage pipeline was used to screen 95 initial isolates based on acid production, biochemical traits, antimicrobial activity, and gastrointestinal resilience. The lead isolate, BDN12, was identified via 16S rRNA sequencing (GenBank PX973265) as Lentilactobacillus farraginis, showing 99.87% identity with strain NRIC 0676. Phylogenetic analysis confirmed its placement within the L. farraginis clade with 100% bootstrap support. In vitro assessments showed that BDN12 maintained viability at pH 3.0 and 0.4% oxgall bile salts. BDN12 neutralized cell-free supernatant exhibited significant (p<0.05) inhibitory activity against Escherichia coli ATCC 25922 (30.33±0.58 mm) and Salmonella enterica ATCC 14028 (29.00±1.00 mm). This inhibitory activity may be attributed to the presence of bacteriocin-like compounds acting as non-acidic antimicrobial factors. Safety profiling confirmed the BDN12 strain was non-hemolytic and susceptible to clinically significant antibiotics. PCR safety screening further confirmed the absence of virulence factors (esp, gelE, fsrB, asa1, cylA, cylM), vancomycin resistance genes (vanA, vanB), and biogenic amine-producing genes (hdc1, hdc2, tdc). These results establish L. farraginis BDN12 as a safe, potent, and locally adapted functional feed additive capable of enhancing poultry health in antibiotic-free production systems.